Ценностно-мотивационные факторы отношения к труду рабочих промышленных предприятий - Дрожанова, О. (Социология: теория, методы, маркетинг, 2007)
The author examines and summarizes theoretical approaches and research methods for measuring attitudes towards labor, pointing their succession and alternation out. Based on materials of a sociological survey conducted among shipbuilding workers,the structure of work motives of an industrial worker in the present socio-economic conditions is identified and analyzed. Value and motivational factors determining workers' attitudes toward labor of the surveyed enterprises, as well as peculiarities of their manifestations have been found. The terminal attitude toward labor is considered as an additional social resource actualizing creative potential of a worker.